Elaboration of an educational technology for ostomized patients: peristomal skin care - Carvalho,Dione Seabra de (2019)
ABSTRACT Objective: to describe the elaboration of an educational technology to support orientations on peristomal skin care for ostomized patients. Method: the research had a qualitative approach and used the Action-Research method; data was collected through the Focus Group technique, with eight ostomized patients. The data was analyzed through Thematic Content analysis. Results: the analysis generated for categories: the educational material as source of knowledge; difficulties in the peristomal skin care; peristomal skin self-care; and educational technology for ostomized patients. Based on these data, the Educational Technology was elaborated. After its validation, it will contribute to the prevention of peristomal dermatitis. Final considerations: we highlight the contribution of educational technologies in the context of health education and the role of this resource to promote health, prevent complications, develop skills and promote patient autonomy and confidence.